Managing Corporate Energy Needs: The Role of Management Accounting (Book). - Dominiak, Geraldine; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "Managing Corporate Energy Needs: The Role of Management Accounting," by Harold E. Wyman and J. Edward Ketz.